Assessment of Urban Growth and Sprawl Using GIS and Remote Sensing Techniques in South Ghor Region, Al-Karak, Jordan - Hammad Abu Ghurah, Mousa; Khairul Amri Kamarudi, Mohd; Abd Wahab, Noorjima; Juahir, Hafizan; Barzani Gasim, Muhammad; Lananan, Fathurrahman; Nizam Abdul Maulud, Khairul; Hafiz Rosli, Mohd; Shakir Mohd Saudi, Ahmad; Ismael Rizman, Zairi; Saupi Mohd Zin, Mohd (International Journal of Engineering and Technology, 2018)
The land is a primary natural resource and is essential for human practice and life on earth. Improvement of land use and land cover is very much helpful to policymakers, city planners and for the sustainability of urban ecosystems. The urbanization process (urban growth and sprawl) is one of the important prime factors of land cover/use change, and it is related to the growth and increase of populations and economic activities. This study aims to assess the urban growth and sprawl in South Ghor, Jordan. Supervised classification techniques were applied for LULC classification using four Satellite images (1972, 1989, 1999 and 2016). The land was classified into four categories agricultural land, pastures and bare land, urban area and water bodies. The supervised classification techniques show that urban area and agricultural land have increased while water bodies and bare land have decreased. They also show the rapid urban growth and sprawl in the study areas.Â Â